Phosphates galore: handle with care - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Eduardo Miller Mendez, Director of the 'Société sénégalaise des phosphates' in Thiès, Senegal, has pointed out that we illustrated the article about phosphates on page 7 of Spore 86 with a photo of his company while 'the offending products...